PERMASALAHAN LINGKUNGAN DAN INFRASTRUKTUR DALAM PEMBANGUNAN DESA TANJUNG SARIBU - hariando, luki; Irfan Sihombing; Frengki Simanullang; Jusup P. Sihotang (LPPM Universitas HKBP Nommensen, 2023)
The Practice and Community Service Lecture (KPPM) activities carried out by HKBP Nommensen University Medan provide significant benefits for various parties involved, namely students, communities, local governments, and universities. For students, KPPM is a means of applying knowledge gained on campus, deepening interdisciplinary knowledge, increasing self-confidence, and building mentality in facing community conditions. Students also have the opportunity to conduct research, service, and develop a mindset to advance the village in the future. For the community, KPPM provides assistance in planning and implementing community development and empowerment, improving thinking and acting skills, and obtaining new ideas for local empowerment. Local governments and partners get suggestions and ideas to improve the village, improve existing problems, and help workers from students to work together in development programs. For universities, KPPM focuses on developing science and technology, facilitating lecturers in research based on concrete problems in the field, collaborating with various agencies, and developing effective research in solving community problems.